Corpos domesticados: a violência de gênero no cotidiano das domésticas em Montes Claros 1959 a 1983 - Santos, Rosana de Jesus dos (2009)
In the present study we analyzed the violence against women in the city of Montes Claros during the period between 1959 and 1983. Through the reading of lawsuits and oral sources and having as the theoretical referential the gender studies, we searched to notice how the relationships were organized in the domestic interior, on what ways violence occurred and how these were treated by the justice. Oral narratives of women who work as maids and lawsuits of body lesion, rapes, violent attempt on shame, homicide, theft and infanticides were analyzed under a feminist perspective. We perceived a preponderance of bosses (men and women) as defendants in the lawsuits analyzed. It became perceivable during the research that the gender conceptions imbricate to the ones of class and ethnic group created asymmetries and based various forms of violence between maids and their bosses (men and women).